Waqf-Based Human Capital and Institutional Sustainability: An Ethnographic Study of Waqf Basyari in Indonesian Pesantren - Eko Nur Cahyo; Usmanul Khakim; Muhammad Faqih Nidzom; Khurun’in Zahro’; Nurita Binti Juhdi (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
Despite extensive studies on voluntarism in Islam and fiqh-based analyses of waqf, self-devotion (waqf basyari) has never been examined as waqf-based human capital nor linked to institutional sustainability within Islamic economics. This study fills this gap by examining waqf basyari and institutional sustainability at Pondok Modern Darussalam Gontor (PMDG), a century-old Indonesian pesantren. Framed within Islamic economics and waqf-based institutional economics, this ethnographic study employs participant observation, interviews, and document analysis. The findings reveal three results. First, the waqf basyari tradition at PMDG has developed over nearly 100 years from the founders' devotion movement. Second, devoted cadres (kader wakaf) realize institutional sustainability across five Panca Jangka dimensions: education, cadre formation, infrastructure, khizanatullah (asset expansion), and family welfare. Third, these cadres possess six attributes—readiness, time commitment, duty acceptance, evaluation openness, prioritizing the pesantren, and institutional defense—that operationalize waqf-based human capital. This study contributes theoretically to Islamic economics by introducing waqf-based human capital as a new analytical category and demonstrating its causal link to institutional sustainability. The findings offer a replicable model for Islamic educational institutions seeking sustainability beyond lineage-based succession.